2007
DOI: 10.1002/casp.922
|View full text |Cite
|
Sign up to set email alerts
|

“If a girl doesn't say ‘no’…”: young men, rape and claims of ‘insufficient knowledge’

Abstract: Most psychological theories of rape tend to stress factors internal to both rapists and their victims in accounting for the phenomenon. Unlike such theories, social psychological and feminist accounts have drawn attention to social and cultural factors as productive of rape, and have criticized psychological accounts on the grounds that they often serve, paradoxically, to cement pre-existing 'common-sense'. In this paper we examine the ways in which young Australian men draw upon widely culturally shared accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 60 publications
(49 reference statements)
2
82
2
1
Order By: Relevance
“…The means of conveying consent or refusal mentioned by these participants are similar to previous findings (e.g. Beres, 2010;O'Byrne et al, 2006) that have demonstrated that non-verbal communication of consent and refusal is well understood by both young men and young women (Kitzinger & Frith, 1999;O'Byrne et al, 2006;O'Byrne et al, 2008). However, they also recognise that other people might read more into these behaviours (see 'Interpreting Consent' theme, below), and they also went on to emphasise the importance to them of verbal consent and refusal.…”
Section: (Sally)supporting
confidence: 83%
See 4 more Smart Citations
“…The means of conveying consent or refusal mentioned by these participants are similar to previous findings (e.g. Beres, 2010;O'Byrne et al, 2006) that have demonstrated that non-verbal communication of consent and refusal is well understood by both young men and young women (Kitzinger & Frith, 1999;O'Byrne et al, 2006;O'Byrne et al, 2008). However, they also recognise that other people might read more into these behaviours (see 'Interpreting Consent' theme, below), and they also went on to emphasise the importance to them of verbal consent and refusal.…”
Section: (Sally)supporting
confidence: 83%
“…However, a common perception was that any man might hope or expect that he was going to have sex with a woman, based on the behaviours discussed, but that this was different to believing that the woman consented. This provides further support for the arguments made against the miscommunication model (Kitzinger & Frith, 1999;O'Byrne et al, 2006;O'Byrne et al, 2008), as these participants gave accounts that suggested that any such claim was grounded in an insincere attempt by a 'bad guy' to justify sexually coercive behaviour, rather than genuine miscommunication.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations